The Effect of Membrane Type on the Performance of Microbial Electrosynthesis Cells for Methane Production. Issue 3 (1st December 2016) - Babanova, Sofia; Carpenter, Kayla; Phadke, Sujal; Suzuki, Shino; Ishii, Shun'ichi; Phan, Tony; Grossi-Soyster, Elysse; Flynn, Michael; Hogan, John; Bretschger, Orianna
Abstract : This study evaluated the influence of the membrane type on the performance of bioelectromethanogenesis reactors. The functional activities and taxonomic composition of bioelectrochemical systems (BES) with Nafion 117 or Ultrex CMI-7000 membranes were assessed. Functional activity was measured as methane production and current consumption rates throughout operation. Microbial biomass and phylogenetic diversity were characterized at strategic intervals related to the membrane type used. The Nafion-BES reactor showed the best performance in terms of current consumption and methane production in the early operational period and a strong selection for fermentative bacteria. However, the Nafion-BES was not able to sustain this activity over the course of 7 subpassages since methanogenic species were ultimately selected against and did not appear in the community composition for the last two subpassages. In contrast, the Ultrex-BES had a lower pH concentration gradient and lower overall current consumption activity; however, the methane production activity from the Ultrex-BES was equivalent or better than the Nafion-BES reactor and was sustained throughout the seven subpassages. The membrane type appeared to be responsible not only for differences in the electrochemical operation of the BESs but it also influenced microbial taxonomic composition and dynamics.